THE CORRELATION BETWEEN STUDENTS’ VOCABULARY ACHIEVEMENT AND READING COMPREHENSION - Valentia, Mega (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is aimed to find out what extend is the correlation between vocabulary achievement and reading comprehension on the 11th grade students of SMA Islamiyah Pontianak in the academic year of 2016/2017. The population of this research was the 11th grade students of SMA Islamiyah Pontianak in the academic year of 2016/2017 with a total number of 47 students. It was divided into two class, XI IPS I and XI IPS II. The sample was class XI IPS I, there are 22 students taken by cluster random sampling technique.  The instruments of this research include instrument try out test and test of vocabulary achievement and reading comprehension. The results of the research show that there is a correlation between students’ vocabulary achievement and students’ reading comprehension. The correlation is positive and significant. The result of the hypotheses test showed that the coefficient of correlation is 0.563 and the total effective contribution of vocabulary mastery is 31%. The significance of F is 3.043 < 2.086.It means that Ho is rejected. Regarding the result of the research, it can be concluded that vocabulary mastery has positive contribution in reading comprehension.  Keywords: Correlation, Vocabulary Achievement, Reading Comprehension